2020
DOI: 10.1097/ijg.0000000000001757
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Saccadic Eye Movements Among the High-tension Glaucoma, Primary Angle-closure Glaucoma, and Normal-tension Glaucoma

Abstract: Précis: Saccadic eye movements were compared between high-tension glaucoma (HTG), normal-tension glaucoma (NTG), and primary angle-closure glaucoma (PACG). Saccades were differently affected between the subtypes of primary glaucoma. Aim: The aim of the study was to compare saccadic eye movements in eyes with HTG, PACG, and NTG. Methods: Saccadic eye movements were recorded using the eye tracker Eyelink-1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…Gain of less than 1 indicates a hypometric saccade, and a gain of more than 1 indicates a hypermetric saccade. Saccade amplitude and gain were lower in glaucoma patients than controls in the three studies, 63 , 64 , 66 and there was no difference between the two studies. 62 , 67 …”
Section: Which Eye Movements Have Been Studied In Glaucoma?mentioning
confidence: 70%
See 4 more Smart Citations
“…Gain of less than 1 indicates a hypometric saccade, and a gain of more than 1 indicates a hypermetric saccade. Saccade amplitude and gain were lower in glaucoma patients than controls in the three studies, 63 , 64 , 66 and there was no difference between the two studies. 62 , 67 …”
Section: Which Eye Movements Have Been Studied In Glaucoma?mentioning
confidence: 70%
“…Ballae et al revealed average velocities of 145°/ms (control: 152°/ms) and peak velocities of 266°/ms (control: 315°/ms) which were statistically significant. 63 Their reporting of degrees per millisecond is interpreted by this review as a misprint and, based on their data, is likely degrees per second. Kanjee et al found no difference in peak saccade velocity and saccade duration when assessing targets within 10 degrees of fixation using binocular eye tracking in a smaller sample size of 16 patients with mild to advanced disease (compared to Ballae et al with a larger sample of uniformly advanced disease).…”
Section: Which Eye Movements Have Been Studied In Glaucoma?mentioning
confidence: 94%
See 3 more Smart Citations